Electrostatic spinning microneedle acne patch and preparation method thereof
By designing electrospinned microneedle acne patch (PT@PCPQC), the synergistic effect of self-powered generators and conductive microneedles has been solved, and the problem of difficult drug spread and antibiotic resistance in existing acne treatments has been achieved, achieving high efficiency , continuous acne healing effect.
Patent Information
- Application Number
- CN202411556068.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Among the existing acne treatment methods, frequent use of antibiotics leads to increased drug resistance, and it is difficult for the drug to spread effectively to the deep skin, resulting in unsatisfactory treatment results.
An electrospinned microneedle acne patch (PT@PCPQC) was designed, which consists of a self-powered generator and conductive microneedle, which uses piezoelectric nanofiber membrane to generate electrical stimulation, and combines conductive microneedle to deliver quercetin. (QC) for anti-inflammatory, antioxidant and antibacterial effects.
The patch significantly improves the efficiency of acne treatment through synergies, enhances the bioavailability of the drug, reduces side effects, and is able to continuously release the drug to accelerate healing.
Smart Images

Figure CN119385987A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biological products, and specifically relates to an electrospinning microneedle acne patch and a preparation method thereof. Background Art
[0002] Acne is a chronic inflammatory skin disease caused by infection with the anaerobic bacteria Propionibacterium acnes (P.acnes). Acne usually presents with symptoms such as dry skin, severe erythema, and skin scarring. Traditional antibiotics with anti-inflammatory or bactericidal properties (erythromycin, clindamycin, benzoyl peroxide) are mainly used to combat acne vulgaris. However, frequent use of antibiotics may increase the resistance of Streptococcus acnes to antibiotics and cause other side effects. In addition, due to the existence of the skin barrier, most drugs cannot be effectively diffused to achieve the desired therapeutic effect. Therefore, there is an urgent need to develop novel therapeutic patches with high drug utilization to improve the therapeutic effect and reduce the side effects in acne healing.
[0003] Recently, more focus has been placed on microneedles (MNs) containing multiple micron-sized needles. MNs can release drug molecules across the skin barrier in a targeted manner, improving transdermal drug delivery efficiency and bioavailability. For example, MNs loaded with AZA acid prepared by Xing et al. showed more significant inflammation resolution than commercially available AZA cream. MNs patches containing salicylic acid (SA) prepared by Zhang et al. showed therapeutic effects in the topical treatment of Pseudomonas acnes infection. MNs may be an effective strategy for the treatment of acne. However, MNs administered alone have certain limitations in acne healing because they cannot regulate cell behavior to accelerate tissue repair. Intercellular communication is regulated by electrical signals between tissues.
[0004] Clinical studies have shown that electrical stimulation (ES) can affect wound healing by promoting cell proliferation and migration. However, since the application of traditional external power ES devices is greatly limited, piezoelectric materials have the characteristics of self-generating electricity under mechanical stress and show great application potential in self-powered dressings. Among them, polyvinylidene fluoride (PVDF) has good piezoelectric effect and good biocompatibility, and is a piezoelectric material with advantages in biomedical applications. For example, Wang et al. proposed a hydrogel composed of self-powered piezoelectric polyvinylidene fluoride (PVDF) and polyvinyl alcohol (PVA). Local piezoelectric stimulation can act on the wound surface, provide positive guidance, and promote wound healing. Therefore, introducing ES therapy into acne treatment is expected to achieve better results. Inspired by these studies, a multiplier effect can be achieved by combining the advantages of MNs and ES in treating acne healing. Quercetin (QC) is a promising drug that is loaded into MNs for acne treatment due to its antioxidant, anti-inflammatory, and antimicrobial activities. Based on these considerations, an all-in-one acne patch (PT@PCP) was designed.QC ), which contains a self-powered generator and conductive MNs to accelerate acne healing. PT@PCP QC The patch consists of two functional layers ( Figure 1 ), the outer layer is a piezoelectric PVDF-TPU (PT) nanofiber membrane prepared by the solution 54 blow spinning (SBS) method, which generates ES when deformed by force. The inner layer is CS / PVP / QCMNs, loaded with conductive poly (3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) / (PCPQC), which effectively delivers QC to kill infectious pathogens (acne bacteria) and achieve anti-inflammatory and antioxidant effects. In addition, the conductive PCPQC1% MNs can transmit the electrical signals of PT to the acne area, enhancing the therapeutic effect. PT@PCPQC1% has excellent drug delivery performance and self-generated characteristics, and may become a new type of patch for the treatment of acne. Summary of the invention
[0005] The purpose of the present invention is to provide an electrospinning microneedle acne patch and a preparation method thereof, that is, to provide an anti-inflammatory, antioxidant, and biocompatible conductive microneedle for treating acne wounds.
[0006] The preparation method of the electrospinning microneedle acne patch provided by the present invention comprises the following steps:
[0007] 1) Chitosan (CS) and polyvinyl pyrrolidone (PVP) with a mass ratio of 1:4 were dissolved in 80% acetic acid solution, and then 1% quercetin (QC) and 1.5% conductive polymer (PEDOT:PSS) were added and stirred overnight to prepare a mixed solution;
[0008] The concentration of chitosan and polyvinyl pyrrolidone added to the acetic acid solution is 10%.
[0009] 2) dissolving polyvinylidene fluoride (PVDF) and thermoplastic polyurethane (TPU) with a mass fraction of 10% and a ratio of 9:1 in N'N-dimethylacetamide solution and stirring overnight to prepare a blow spinning solution;
[0010] 3) The mixed solution in 1) above was placed in a microneedle model by solution casting, and dried in a vacuum oven at 60° C. for 8 h to form microneedles.
[0011] 4) The microneedles prepared in 3) are peeled off from the model and placed on a solution blowing receiving device, and the blowing solution in 2) forms a layer of piezoelectric nanofibers on the microneedle base, thereby preparing a multifunctional self-powered microneedle acne patch.
[0012] Furthermore, antimicrobial peptides are also added in the step 1);
[0013] The antimicrobial peptide is obtained by modifying the scorpion toxin antimicrobial peptide La39, and its specific amino acid sequence is FPFKLSLIPIAISPLKKL (SEQ ID NO: 1).
[0014] PT@PCP provided by the present invention QC1% -LA MNs patch, which has a synergistic effect of drug and electroactivity, has a significant inhibition rate against acne pathogens, Staphylococcus aureus and Escherichia coli, and has excellent antioxidant and anti-inflammatory properties, long drug release duration and good biocompatibility, providing a simple and effective treatment strategy for acne repair. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 (a)CPQC1%, (b)CP, (c)PCP QC1% and (d)PT@PCP((I)PCP QC1%QC1% Digital images and SEM images of 10×10 MNs array and (II) PT nanofiber membrane. (e) FTIR spectra and (f) XRD curves of QC, CP, CPQC1%, PCPQC1%, and PT.
[0016] Figure 2 :(a) Water contact angle, (b) Water absorption rate, (c) Loading force-displacement curves of different samples. (d) Brightness and fluorescence images of pig skin after applying CPMNs patch loaded with or without sodium fluorescein. (e) Schematic diagram of QC release from inserted MNs patch.
[0017] Figure 3 :(a) Schematic diagram of the piezoelectric effect of the PT layer. (b) The linear relationship between Voc and the force of the PT layer. (c) Voc of the PT layer under different forces. (d) CP, CP QC1% and PCP QC1% (e) PT@PCP QC1% Photo of a light bulb that glows.
[0018] Figure 4 :(a)QC from CP, CP QC1% -LA, PCP QC1% -LA and PT@PCP QC1% -The cumulative release of LA. (b) Colony count and (c) CP, CP QC1% -LA, PCP QC1% -LA and PT@PCP QC1% -The antibacterial rate of LA against Staphylococcus aureus, Escherichia coli and P.saureus.
[0019] Figure 5:(a) Absorbance of DPPH solution at 517nm after 2h reaction with different samples. (b) Antioxidant rate of different samples. (c) Linear calibration OD value curve of IL-6. (d) Expression of IL-6 in RAW264.7 cells treated with different samples.
[0020] Figure 6 :(a) Fluorescence images of L929 cells cultured with different samples. (b) Cell viability of L929 cells cultured with different samples for 24h and (c) 48h. DETAILED DESCRIPTION
[0021] The present invention is described in detail below in conjunction with specific embodiments and drawings.
[0022] Example 1: PT@PCP QC1% Patch production
[0023] 0.8 g CS / PVP (w / w ratio of 2:8), 8 mg QC and 0.8 g CS / PVP (w / w ratio of 2:8) with different PEDOT:PSS contents (4 mg, 8 mg, 12 mg), 8 mg QC and 0.8 g CS / PVP (w / w ratio of 2:8) were dissolved in a mixed solvent containing AC / DI (w / w ratio of 8:2). 1% QC-loaded CS / PVP showed the best antibacterial effect and was selected for further study. The solution was poured into a PDMS micromold (10×10 array, 600 μm height, 300 μm base width) and degassed in a vacuum oven to prepare the patch. Then, the patch was dried at 40°C for 8 h and finally peeled off from the PDMS micromold. The obtained patches were named CP, CP QC1% and PCP QC1% 1.5 g PVDF / TPU (PT) (w / w ratio of 9:1) was added to DMAc solvent and stirred overnight. Then, air bubbles were removed by ultrasonication. QC1% PT nanofiber membrane was formed on the surface of MNs. The spinning speed was 6 mL / h and the wind speed was 40 slpm. The final PT@PCP QC1% The patch was dried in a vacuum oven at 35 °C for 24 h to completely remove the solvent.
[0024] Example 2: PT@PCP QC1% Properties of the patch
[0025] 1. Morphology and structure
[0026] The morphology of different samples was observed by scanning electron microscopy (SEM, Netherlands; using Regulus8100, Japan). The chemical and crystal structures were characterized by Fourier transform infrared spectroscopy (FTIR, Nicolet ISO, USA) and X-ray diffraction (XRD, 84 Rigaku Smart Lab, Japan).
[0027] Different MNs patches (CP, CP QC1% and PCP QC1% ) digital images and SEM images such as Figure 1 (ac) Optical photos show that the CPMNs patch without QC is transparent ( Figure 1 (a)), the color changes due to the addition of QC and PEDOT:PSS. QC1% MNs patch is yellow, PEDOT:pss loaded PCP QC1% MNs patch is yellow-brown ( Figure 1 (c)). In addition, CP, CP QC1% and PCPM QC1% The morphology of Ns is conical, as shown in the SEM images ( Figure 1 (ac)). The microneedles on the MNs patch are conical, smooth, and crack-free ( Figure 1 (ac)). The height of MNs is about 600 μm ( Figure 1 (ac)), can penetrate the stratum corneum and epidermis (~100μm) of the skin to reach the dermis and deliver QC to the acne wound. PT nanofibers prepared by solution blowing (SBS) are well oriented. Since SBS can achieve local stretching and polarization during the spinning process, the piezoelectricity of PT nanofibers can be significantly improved without further polarization treatment. Conductive PCP QC1% The MNs patch is combined with the PT piezoelectric layer to introduce the electrical stimulation generated by the PT layer into the acne wound surface. QC1% Suggested cross-sectional SEM shows PT layer and PCP QC1% MNs are positively laminated ( Figure 1 (d)). A novel integrated acne patch consisting of conductive MNs and a self-powered PT layer was proposed for transdermal drug delivery of QC and accelerated acne healing.
[0028] The FTIR spectra of each sample are shown in Figure 1 (e) In CP MNs, the absorption peaks of PVP and CS are located at 2885–2956 cm -1 (CH stretching of aliphatic compounds) and 1623 cm -1 (acetyl stretching vibration), which is consistent with the literature report. It is worth noting that 1383cm-1 The significant characteristic peak at (OH bending vibration of phenol functional group) is attributed to CP QC1% QC added in. In addition, (3033-3632cm -1 ) is attributed to the intermolecular hydrogen bonds between OH and NH among CS, QC, and PVP. QC1% pp at 1639cm -1 、1086cm -1 and 1044cm -1 New peaks appeared at , corresponding to the C=C plane vibration of PEDOT thiophene and phenyl ring, and S=O and SO vibration of PSS sulfonic acid group. FTIR spectrum showed that QC and PEDOT:PSS were successfully loaded into PCPM QC1% In addition, PVDF is available in 841, 1072, 1174 and 1402 -1 The characteristic peak at corresponds to the polar β-phase crystal structure, indicating that there is high stretching during the solution blowing process. The electroactive β-phase PT layer formed gives the PCPMNs a piezoelectric effect. The XRD curves of each QC1% sample are shown in Figure 2 QC exhibits X-ray diffraction peaks at 2θ = 10.72°, 12.44°, 23.27° and 27.34°, indicating that it is crystalline. QC1% n and PCP QC1% In mn, the X-ray diffraction peak of QC disappears, indicating that QC is mainly wrapped in the CP matrix. QC1% Compared with ns, the addition of PEDOT:PSS has a significant effect on PCP QC1% The X-ray diffraction peaks of MNs were not affected. In addition, the X-ray diffraction peaks of PT at 20.6° and 22.6° corresponded to the (200) and (111) crystal planes of β-phase PVDF, indicating the existence of a polar β-phase crystal structure in PT.
[0029] 2. Physical properties
[0030] The water absorption rate of each sample was measured at room temperature using the humidity method. Each sample was weighed (m0) and soaked in phosphate buffered saline (PBS, pH = 7.4) for 3 hours. Each sample was then removed and the excess PBS on the surface was removed using qualitative filter paper and then weighed immediately (m1). The water absorption rate of each sample was calculated using the following formula: (1):
[0031] Waterabsorptionrate(%)=×100(1)
[0032] The compression test was performed by a universal testing machine (INSTRON3382, USA) to test the mechanical strength of each sample. The samples (labeled with 1% sodium fluorescein) were inserted into the pig skin and peeled off after 1 minute to further evaluate the skin penetration performance of MNs. In addition, the pig skin tissue was observed under bright light and UV (λ = 254nm). Hydrophilic dressings can remove exudate and maintain a moist wound healing environment. The hydrophilicity of the samples was studied by water contact angle (WCA) and water absorption. Figure 2 As shown in (a), the outer PT layer is hydrophobic with a WCA of 132.8°±2.42°. QC1% and PCP QC1% It is hydrophilic, with a WCA of about 60°, which is due to the abundant hydrogen bonds in CS and PVP. QC1% and PCP QC1% The hydrophilicity of the layer is not greatly affected. Figure 2 (b) It can be seen that the water absorption rate of CP MNs is the highest (1007.96±11.96%). QC1% The water absorption rate of MNs decreased slightly to 807.66 ± 125.74%, which was due to the fact that a small amount of poorly water-soluble QC on the surface of MNs weakened the entry of water molecules. QC1% The water absorption rate of PCP remains similar. QC1% In comparison, PT@PCP QC1% The water absorption rate of slightly decreased to 752.40±23.07, which is because the composite PT layer is hydrophobic. Apply PT@PCP on the acne wound QC1% Maintain a suitable moist environment.
[0033] The mechanical strength of MNs is essential for penetrating the skin. Therefore, the mechanical strength of different MNs was measured by axial compression test. From the slope change trend of the force-displacement curve ( Figure 2 (c)) It can be seen that CP QC1% and PCP QC1% It is stronger than CP, indicating that the addition of QC and PEDOT:PSS enhances the rigidity of MNs. QC1% and PCP QC1% The morphology of MNs before and after applying different loads (0.1, 0.2, and 0.5 N) further demonstrated the improvement of their stiffness. QC1% and PCP QC1% Under a loading force of 0.5 N, an obvious fracture surface is presented, indicating that CP QC1% and PCP QC1%Has higher skin penetration stiffness.
[0034] In addition, sodium fluorescein (NaFL) was loaded into MNs to simulate QC release. The MNs patch was pressed into the pig skin with the thumb for 1 min to evaluate its actual use effect on the skin. After applying MNs, microchannels ( Figure 2 (d)). In addition, the NaFL-loaded MNs showed bright fluorescence signals (λ = 254 nm) under UV radiation, indicating that the loaded NaFL effectively diffused from the MNs patch into the pig skin ( Figure 2 (e)). These results confirm that MNs patch has the potential to promote effective QC delivery for the treatment of acne.
[0035] 3. Piezoelectric and conductive effects
[0036] The piezoelectric effect of the PT nanofiber layer was characterized using an electrochemical workstation (CHInstruments, China). Two layers of high-purity copper foil (thickness 20 μm) were directly laminated on both sides of the sample (2 × 297 cm 2 , 1mm thickness). The open circuit voltage of the samples was measured at 10g (0.1N), 20g (0.2N), 50g (0.5N), 100g (1N) and 200g (2N) weights. In addition, the resistance of MNs with different PEDOT:PSS contents was tested by the electrochemical impedance spectroscopy (EIS) method. The conductivity of different samples was calculated by the following formula:
[0037]
[0038] where σ is the conductivity, L is the distance between the two electrodes, S is the cross-sectional area of the esch sample, and R is the resistance of MNs with different PEDOT:PSS contents.
[0039] During compression and release, the intrinsic dipole moment allows surface charge transfer, resulting in a piezoelectric potential of PT ( Figure 3 (a)). Under different oc forces, PT increases linearly with the increase of force ( Figure 3 (b)). Under the force of 0.1N, the voltage of the PT layer is measured to be about 0.6V oc , indicating that its response to small forces is stable. The sensitivity of V to force is 1.806, and the linear fitting coefficient oc(R 2 ) is 0.982. In addition, under a series of mechanical forces (0.1-2N), by precisely controlling the cyclic pressure oc The V( Figure 3 (c)). Under the force of 0.1~2N, the V generated by the PT layer gradually increases from 0.63V to 3.73V, indicating that ocThe PT layer can provide continuous and stable electrical stimulation for acne healing.
[0040] In addition, the electrical signals formed by the PT layer need to be transmitted to the acne site to promote acne healing. QC1% The conductive properties of MNs were tested. As the PEDOT:PSS content increased from 0 to 1.5%, the intrinsic impedance of MNs showed a downward trend. At the same time, as the PEDOT:PSS incorporation increased from 0% to 1.5%, the conductivity of MNs increased from 0.002±0.0004mS / cm to 0.41±0.02mS / cm. In addition, PCPM QC1% Ns can be used as a connecting conductor in a circuit to light a bulb ( Figure 3 (e)). These results suggest that MNs have excellent electrical conductivity, which is beneficial for the transmission of electrical stimulation in the PT layer and promotes acne healing.
[0041] Example 3: Preparation of antimicrobial peptides
[0042] The polypeptide extracted from the Australian chain tail scorpion - scorpion toxin antimicrobial peptide La39, which consists of 18 amino acids and the sequence is FPFLLSLIPSAISALKKL. It has been reported to have inhibitory activity against Staphylococcus aureus, no inhibitory activity against Escherichia coli, and hemolytic activity.
[0043] The sequence was sent to a biological company for synthesis to obtain the target gene, which was then amplified by PCR. After the gene was digested with XhoⅠ and XbaⅠ, it was combined with the vector plasmid pPICZα-A that was also digested with double enzymes to form the positive plasmid pPICZα-A–La, which was verified to be correct by sequencing. Take the Pichia cells and inoculate them on the antibiotic-free YPD plate using the three-segment streak method, and culture them at 30℃ for 72 hours. Pick a single colony (preferably containing a satellite colony) from the third streak area to 35ml YPD liquid culture medium, and shake it at 32℃ and 300r / min overnight. Then inoculate 1ml of the overnight culture solution into 100ml YPD liquid culture medium and culture it overnight under the same conditions. When the OD600 value of the bacterial solution reached about 1.3, the competent cells were prepared. After centrifugation, double distilled water and D-sorbitol resuspension, Pichia competent cells with OD600=1.00 were finally obtained.
[0044] The recombinant vector plasmid was extracted and digested with SacⅠ, and the digestion products were detected by 1% agarose gel electrophoresis. The remaining product was added with water to 200μL, extracted with phenol, phenol:chloroform, and chloroform in turn, and precipitated with NaAC and ethanol. After centrifugation and washing, it was resuspended to 1μg / μL. Take 10μg of single-enzyme digestion plasmid and mix it with 80μL competent cells, add it to the pre-cooled electroporation cup, and place it on ice for 5min before electroporation (1.5kV, 200Ω, 25μF). After electroporation, sorbitol was added and mixed, and cultured for 2h. The transformant was inoculated on a YPDS plate containing bleomycin and cultured at 30℃ for more than 72h. At the same time, the empty vector was linearized and electrotransformed into Pichia pastoris as a control. The positive recombinant Pichia pastoris was inoculated on a YPDS plate containing bleomycin, and a single colony was picked to be cultured in liquid culture medium. PCR amplification was performed using the yeast genome as a template, and the results showed that the target gene was correctly integrated.
[0045] The positive recombinant expression strain was inoculated into YPD liquid medium for overnight culture, and then inoculated into BMGY medium until OD600 reached 4-8. The cells were collected by centrifugation, resuspended in BMMY medium and induced for 96 hours, during which methanol was added and sampled regularly. After induction, the supernatant was collected by centrifugation. The supernatant was purified by His tag, mixed with the purification column filler overnight, and flow-through, washing, elution, and collection of each liquid were performed the next day. After methanol induction, gel electrophoresis was used to verify the expression of the antimicrobial peptide La39-A.
[0046] The antimicrobial peptide La39-A solution was diluted to 6 different concentrations with PBS, so that the final concentrations of the extract were 200, 100, 50, 25, 12.5, and 6.25 μg / mL, respectively, and mixed with 100 μL of 10 4 CFU / mL of Staphylococcus aureus, Escherichia coli and Salmonella were added to a 96-well plate and cultured in a constant temperature incubator at 37°C for 12 hours. The lysis of the antimicrobial peptide La39-A against various pathogens was measured. As shown in Table 1, the MIC of the modified peptide La39-A against Staphylococcus aureus was increased to 25 μg / mL, and it also had good antibacterial properties against Escherichia coli and Salmonella.
[0047] Table 1: Antibacterial performance of antimicrobial peptide La39-A
[0048] Dilution concentration (μg / mL) 200 100 50 25 12.5 6.25 Escherichia coli + + + + - - salmonella + + + - - - Staphylococcus aureus + + + + - -
[0049] Fresh rabbit blood samples were collected, centrifuged, washed three times with Hepes-NaCl buffer, and then resuspended to a concentration of 10 7 / ml. Next, the suspension was evenly distributed into a 96-well plate, and 100 μL was added to each well. Then, 25 μL of the peptide solution was added to each well at a volume ratio of 4:1, so that the final mass concentration of the peptide reached 200, 100, 50, 25, 12.5 and 6.25 μg / mL, respectively. At the same time, a positive control group was set up using 1% TritonX-100 solution; a negative control group used 0.85% NaCl solution. Three replicates were set for each concentration group and control group to observe the hemolytic activity of the antimicrobial peptide La39-A.
[0050] The results of the hemolysis experiment showed that the positive control group produced hemolysis; while the polypeptide La39-A group had no hemolysis. The results showed that polypeptide La39-A did not produce hemolysin and was relatively safe.
[0051] Example 4: PT@PCP QC1% -LA patch performance
[0052] 1. Drug release effect test
[0053] Adding peptide La39-A to PT@PCP QC1% In the patch preparation step 1, PT@PCP is made QC1% -La patch. Each sample (30 mg) was incubated and shaken in 15 ml PBS solution. At predetermined time intervals, the absorbance of the removed 2 ml PBS solution at 374 nm was measured using a UV spectrophotometer (U-3900HHITACHI, Japan). At the same time, an equal amount of fresh PBS was added to the 2 ml PBS solution. In addition, a linear calibration absorbance curve of QC-LA content was established by evaluating different concentrations of QCPBS solution at 374 nm. According to the linear calibration absorbance curve, the release concentration of QC-LA was calculated. The cumulative release of QC-LA was evaluated using the linear calibration absorbance curve and the following formula:
[0054]
[0055] Where V0 is the volume of the release medium (15 mL, PBS), V e is the replacement volume (2 mL, PBS), n is the number of PBS changes, and C is the i-th sampling time. QCi All experiments were repeated three times.
[0056] Drug release at the acne site is one of the most effective ways to accelerate acne healing by controlling bacterial infection and reducing inflammatory responses. Figure 4 (a) The cumulative release of QC-LA was calculated based on the linear calibration absorbance curve at 374 nm. Figure 4(a) is the QC-LA release of different samples after immersion in PBS solution for 48 hours. QC1% -LA and PCP QC1% -LA MNs had a similar increasing trend of cumulative drug release in the same time interval, indicating that the addition of PEDOT:PSS did not affect the release of QC-LA. QC1% -LA and PCP QC1% The cumulative release of QC-LA from PCP- and LA-MNs was 340.96±25.81μg and 332.21±50.19μg, respectively. QC1% -LA compared to PT@PCP QC1% The QC-LA release of -LAslightly was reduced to 263.93±36.52μg, which was due to the fact that the hydrophobic PT nanofiber network hindered the infiltration of PBS and delayed the release of QC-LA. These results were consistent with the bright fluorescence signal, indicating that QC-LA could be released into the acne wound surface.
[0057] 2. Antibacterial effect test
[0058] The antibacterial effect of each sample was determined by the dynamic contact method. The experimental strains (Staphylococcus aureus, Escherichia coli and P. acnes) were cultured overnight in a fluid culture medium at 37°C and 150rpm. Each sample (5 mg) was co-cultured with the bacterial solution (100 μL) for 3 hours, and then the sample was washed with 5 mL PBS. The treated or untreated bacterial eluate (100 μL) was inoculated onto a blank plate for culture. After 24 hours, the number of viable colonies was counted. The antibacterial activity was calculated as follows:
[0059]
[0060] Sc and Ss are the colony counts of untreated and treated samples. All experiments were repeated three times.
[0061] Since Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli) are common bacteria that easily cause wound infection, and P. acnes is the main pathogenic bacteria that causes acne, we tested the antibacterial effects of different samples on Staphylococcus aureus, E. coli and P. acnes. QC1% -LA and PT@PCP QC1% -LA treatment reduced the number of bacterial colonies. Figure 4 As shown in (c), the antibacterial rates of CP MNs against Staphylococcus aureus, Escherichia coli and Pseudomonas acnes were 43.35%, 75.25% and 42.59%, respectively, which was due to the positively charged amine groups in CS. QC1%The antibacterial rates of -LA MNs against Staphylococcus aureus, Escherichia coli and Streptococcus acnes were increased to 99.02%, 97.75% and 99.67%, respectively. In addition, the addition of PEDOT:PSS and PT to PT@PCP QC1% -LA had no effect on the antibacterial activity. PT@PCP QC1% -LA had an antibacterial rate of 99.80%, 99.5% and 99.83% against Staphylococcus aureus, Escherichia coli and P. acnes, respectively. These results prove that PT@PCP QC1% -LA can achieve antibacterial effects during the healing process of acne.
[0062] 3. Antioxidant effect test
[0063] Each sample (10 mg) was incubated in a DPPH alcohol solution (5 mL) in the dark. The blank control was a DPPH alcohol solution without sample. The absorbance of each sample treatment solution (517 nm) at 0.5, 1, 2, and 3 h was measured using a UV spectrophotometer (U-3900HHITACHI, Japan). The antioxidant activity was calculated using the following formula:
[0064]
[0065] Where control, sampleA and A are the absorbance of the untreated solution and the treated sample, respectively. All tests were repeated three times.
[0066] A large amount of reactive oxygen species (ROS) can cause hypoxia in acne wounds, accelerate the excessive proliferation of pathogenic bacteria (P. acnes), and induce severe inflammatory reactions. Therefore, the antioxidant activity of different samples was tested ( Figure 5 (ab)). Compared with the blank control group and CP, CP QC1% -LA, PCP QC1% -LA and PT@PCP QC1% -LA's absorbance at 517 nm decreased significantly ( Figure 6 (a)), indicating that the incorporated QC-LA has a higher antioxidant activity. In addition, CP QC1% -LA and PCP QC1% -LA's antioxidant rates were significantly increased to 86.59% and 86.58% ( Figure 5 (b)). The improvement of antioxidant rate can be attributed to the phenolic hydroxyl-rich QC-LA providing hydrogen to reduce free radicals. PT@PCP QC1% -LA's initial antioxidant rate is lower than CP QC1% -LA and PCP QC1% -LA, corresponding to a lower cumulative QC-LA release within 2 h. After 2 h, with the increase in QC-LA release, PT@PCP QC1%-LA's antioxidant rate increased to 86.71%, and finally with CP QC1% -LA and PCP QC1% -LA has the same antioxidant rate. In addition, PT@PCP QC1% The color of the DPPH solution treated with -LA changed from the initial purple to yellow, further confirming that PT@PCP QC1% -LA has excellent antioxidant activity.
[0067] 4. Anti-inflammatory effect test
[0068] RAW264.7 cells were treated with lipopolysaccharide (LPS) to study the anti-inflammatory effects of each sample. RAW264.7 cells were cultured in Dulbecco's Modified Eagle Medium (DMEM) at 37°C and 5% CO2 in a cell culture incubator, and the blank group was not intervened. RAW264.7 cells stimulated with LPS (1 μg / mL) were used as LPS-model to prove that the inflammatory model was successfully established. LPS-models treated with different extraction methods were the experimental groups. IL-6 expression values were evaluated according to the instructions of the ELSIA kit.
[0069] Since macrophages play an important role in inflammation and immune regulation, we studied the effects of different samples on the secretion of inflammatory factors by LPS-stimulated macrophages (RAW264.7 cells). First, a linear calibration OD value curve of IL-6 was established ( Figure 5 (c)). Figure 5 As shown in (d), the LPS model significantly increased the expression of IL-6, indicating that inflammation was successfully induced. In addition, the IL-6 expression level in the CP group was slightly reduced because the addition of CS could inhibit the inflammatory response. QC1% -LA and PCP QC1% -LA showed a similar inhibitory effect on IL-6 secretion, which was attributed to QC-LA regulating inflammatory signaling pathways through antioxidants and promoting the activation of heme oxygenase-1 (HO-1). QC1% -LA significantly inhibited the expression of IL-6, indicating that PT@PCP QC1% -LA has good anti-inflammatory activity.
[0070] 5. Cytotoxicity test
[0071] The cell counting kit 8 (CCK-8) method was used to study the cytotoxicity of each sample. Each sample was exposed to ultraviolet (UV) for 2 hours before detection. The extract of each sample was extracted according to ISO10993-5:2009. The mouse fibroblast cell line L929 was co-cultured with culture medium in a 96-well plate. At specific culture times (24h and 48h), CCK-8 reagent (02571100, EPIZYME) was added to each well. After incubation for 2h, the absorbance at 450nm was measured by a microplate reader, and the cells were stained with an AM / PI kit to more intuitively present the morphology of live and dead cells.
[0072] Good biocompatibility is a basic requirement for dressing applications. The cell compatibility of different samples was evaluated by live / dead staining and CCK-8 assay ( Figure 6 ). Figure 6 (a) shows that after L929 cells were cultured with the extracts of each sample for 24 h, almost no dead cells (red) were observed. Most of the living cells were stained with green fluorescence, indicating that CP, CP QC1% -LA, PCP QC1% -LA and PT@PCP QC1% -LA has high cell compatibility. In addition, Figure 6 The cell viability of L929 cells cultured in different sample extracts for 24 h and 48 h is shown. QC1% -LA cell viability was above 95%, similar to that of the blank group, further confirming the QC1% - Cytocompatibility of LA.
Claims
1. An electrospinning microneedle acne patch, characterized in that: The preparation method of the electrospinning microneedle acne patch comprises the following steps: 1) dissolving chitosan and polyvinyl pyrrolidone in 80% acetic acid solution, then adding quercetin and conductive polymer and stirring overnight to prepare a mixed solution; 2) dissolving polyvinylidene fluoride and thermoplastic polyurethane in N'N-dimethylacetamide solution and stirring overnight to prepare a blow spinning solution; 3) placing the mixed solution in 1) above into a microneedle model by solution casting, and drying in a vacuum oven at 60° C. for 8 h to form microneedles; 4) The microneedles prepared in 3) are peeled off from the model and placed on a solution blowing receiving device, and the blowing solution in 2) forms a layer of piezoelectric nanofibers on the microneedle base, thereby preparing a multifunctional self-powered microneedle acne patch.
2. The electrospinning microneedle acne patch according to claim 1, characterized in that: The mass ratio of chitosan to polyvinyl pyrrolidone in 1) is 1:
4.
3. The electrospinning microneedle acne patch according to claim 1, characterized in that: In the above 1), the concentration of chitosan and polyvinyl pyrrolidone added to the acetic acid solution is 10%.
4. The electrospinning microneedle acne patch according to claim 1, characterized in that: In the above 1), 1% quercetin and 1.5% conductive polymer are added.
5. The electrospinning microneedle acne patch according to claim 1, characterized in that: In the above 2), polyvinylidene fluoride and thermoplastic polyurethane with a mass fraction of 10% and a ratio of 9:1 are dissolved in N'N-dimethylacetamide solution.
6. The electrospinning microneedle acne patch according to claim 1, characterized in that: Antimicrobial peptides are also added to the above 1).
7. The electrospinning microneedle acne patch according to claim 6, characterized in that: The amino acid sequence of the antimicrobial peptide is SEQ ID NO: 1.
Citation Information
Patent Citations
Needle array devices and related methods
CN115485013A
Functional double-layer nanofiber membrane prepared by solution blowing spinning and application of functional double-layer nanofiber membrane
CN117488479A
Drug-loaded polyvinylpyrrolidone microneedle as well as preparation method and application thereof
CN118236317A
Microneedle array enhanced controllable self-generating artificial nerve conduit and preparation method thereof
CN118787788A
Acne is micropin high -frequency system for disease treatment
CN208611595U